Validitas Modul Proyek â€œLegenda Surabayaâ€ Berbantukan Qr Code Kurikulum Merdeka Fase B - Mahmudi, Ahmad; Yuwana, Setya; Indarti, Titik; Hendratno, Hendratno (Universitas Muhammadiyah Surabaya, 2023)
Validity of